Experimental investigation of heat transfer augmentation using multiple arcs with gap on absorber plate of solar air heater. (September 2016) - Pandey, N.K.; Bajpai, V.K.; Varun,
Highlights: Nusselt number and friction factor study has been done on roughened solar air heater. A new type of roughness geometry has been developed and investigated. Correlations were also developed for Nu and f . Abstract: In this present article an experimental study has been carried out on heat transfer and friction factor in rectangular channel which is having multiple-arc shaped with gaps as roughness element. The investigation encompassed Reynolds number ( Re ) ranges from 2100 to 21, 000 (7 values), relative roughness height ( e / D ) ranges from 0.016 to 0.044 (4 values), relative roughness pitch ( p / e ) ranges from 4 to 16 (4 values), arc angle ( α ) values are 30–75° (4 values), relative roughness width ( W / w ) ranges from 1 to 7 (5 values), relative gap distance ( d / x ) values are 0.25–0.85 (4 values) and relative gap width ( g / e ) ranges from 0.5 to 2.0 (4 values). The maximum increment in Nusselt number ( Nu ) and friction factor ( f ) is 5.85 and 4.96 times in comparison to the smooth duct. Utilizing these data, correlations were developed for Nu and f .